The Amorites and the Bronze Age Near East : the making of a regional identity - Burke, Aaron A. (Cambridge University Press, 2021)
In this book, Aaron A. Burke explores the evolution of Amorite identity in the Near East from ca. 2500-1500 B.C. He sets the emergence of a collective identity for the Amorites, one of the most famous groups in ancient Near Eastern history, against the backdrop of both Akkadian imperial intervention and declining environmental conditions during this period. Tracing the migration of Amorite refugees from agropastoral communities into nearby regions, he shows how mercenarism in both Mesopotamia and Egypt played a central role in the acquisition of economic and political power between 2100 and 1900 B.C. Burke also examines how the establishment of Amorite kingdoms throughout the Near East relied on traditional means of legitimation, and how trade, warfare and the exchange of personnel contributed to the establishment of an Amorite koiné. Offering a fresh approach to identity at different levels of social hierarchy over time and space, this volume contributes to broader questions related to identity for other ancient societies.